Pengembangan Media Pembelajaran Geografi Berbentuk Buku Infografis Pada Materi Siklus Hidrologi Kelas X SMA Negeri 1 Bukal - Lasman, Sulistiawati; Nurfaika, Nurfaika; Kobi, Wiwin (-, 2025)
The development of learning media is a crucial effort in improving the quality of the learning process, particularly in Geography. The general background of this research is the low interest and understanding of students regarding the hydrological cycle material, which is caused by learning media that are less engaging and less interactive. Specifically, at SMA Negeri 1 Bukal, the use of conventional learning media has not been able to facilitate students in comprehensively understanding the concept of the hydrological cycle. The knowledge gap found is the lack of learning media that combines informative visualization and ease of access, making it difficult for students to internalize the material. In this study, we developed learning media in the form of an infographic book specifically designed for the hydrological cycle material for class X. This infographic book integrates images, diagrams, and concise, easy-to-understand text to help students visually and systematically understand the hydrological cycle process. The development results show that this medium effectively improves students' understanding and their learning interest in the hydrological cycle material. In addition, this medium also makes it easier for teachers to deliver material in a more engaging and interactive way. The implication of this research is the importance of developing innovative learning media that are tailored to the needs of students to improve the quality of Geography learning, especially in the hydrological cycle material, so that it can support the optimal achievement of learning competencies